Social branding framework to address smoking among alternative peer crowd teens. Issue 3 (27th May 2021) - Stalgaitis, Carolyn Ann; Jordan, Jeffrey Washington; Djakaria, Mayo; Saggese, Daniel J.
Abstract : Purpose: This paper aims to describe the Social Branding framework, which uses lifestyle branding to change behaviour within psychographically-defined target audiences. Syke, a Social Branding programme to reduce cigarette use within the higher-risk alternative teen peer crowd in Virginia, USA, is presented as a case study with evaluation results. Design/methodology/approach: Social Branding first creates an authentic lifestyle brand that appeals to a psychographically-defined audience. Once sociocultural authority is built, the lifestyle brand introduces tailored behavioural messaging using targeted messaging channels, relying on experiential marketing events and in-group influencers to align the desired behaviour with the audience's social identity and values. The evaluation consisted of annual cross-sectional surveying (2011–2014; n = 2, 266) on brand recall, liking, message comprehension and current smoking. Among those with recall, the prevalence of liking/comprehension categories (disliked and did not understand; liked or understood; liked and understood) and of smoking within categories was compared across years using chi-square tests. Multivariate logistic regression explored liking/comprehension as a predictor of smoking. Findings: Recall, liking and comprehension were significantly higher in 2014 than in 2011, as was the proportion who both liked and understood Syke. Those who liked and understood Syke had half the odds of current smoking compared to those who disliked and did not understand it. Originality/value: Syke reached, was liked by and was understood by the target audience. The Social Branding framework effectively appeals to and reaches higher-risk audiences, with learnings applicable to other behaviours and populations.